Characterizing contemporary evolutionary change in a recently isolated population of threespine stickleback (Gasterosteus aculeatus L.) - Aspen M. Kozak; Tegan N. Barry; Brenna C.M. Stanford; Sean M. Rogers; Heather A. Jamniczky (FACETS, 2024)
The parallel evolution of lateral plates and body shape in the threespine stickleback (Gasterosteus aculeatus) is an iconic example of adaptation. We test a case of contemporary evolutionary transition in a recently isolated population of marine G. aculeatus in British Columbia, Canada. We investigate Ectodysplasin (Eda) genotypes, plate counts, neutral genetic divergence, and whole-body phenotypes to determine the genetic and phenotypic distance between this population and nearby comparative populations. Our focal population is in the process of adapting both genetically and phenotypically to a freshwater environment, and we provide an example of the genetic basis for parallel evolution on a contemporary timescale. The frequency of Eda genotypes and lateral plate phenotypes in our focal population is not consistent with those of marine or fully freshwater populations. Although our focal population is genetically distinct from nearby marine populations, these fish still more closely resemble marine populations in overall body shape while demonstrating an intriguing intermediate phenotype. Eda frequency and lateral plate phenotype change faster than body shape in response to freshwater conditions, suggesting that the pace of adaptation differs across traits in response to the same environmental conditions. Our results further bolster the case for G. aculeatus as a key model of contemporary evolution.